First-year students working with exemplars: promoting self-efficacy, self-monitoring and self-regulation. Issue 1 (2nd January 2019) - Hawe, E.; Lightfoot, U.; Dixon, H.
Abstract: In this paper, we explore first-year undergraduate students' experiences and perceptions regarding the use of exemplars, with reference to the development of student self-regulation. The study was carried out at a tertiary education institution in New Zealand where the second author was a lecturer. This author used exemplars with two classes of first-year students enrolled in a core introductory paper taught as part of the students' undergraduate business studies degree. Data were gathered through three complementary approaches: students' responses to a short anonymous survey at the end of each of the four sessions where exemplars were used, written notes in the teacher's Teaching journal and semi-structured interviews with student volunteers. When strategically employed as part of the teaching design, it was found that exemplars have the capacity to motivate, enhance students' self-efficacy, promote understanding of task requirements, expand knowledge, understanding and skills in relation to the structure of academic tasks, support and advance subject knowledge, and develop evaluative and productive knowledge and expertise. We concluded the use of exemplars with these students demonstrated their potential as tools for the promotion of student self-efficacy, self-monitoring and to a lesser extent, self-regulation.